Sea creatures of the Southern deep : a novel - Rose-Innes, Henrietta (Department of English Language and Literature, 2016)
This dissertation consists of a short novel, Sea Creatures of the Southern Deep, accompanied by a preface. In the preface, I discuss some aspects of my own experience that have influenced the text. I also outline the development of the manuscript, illustrating the process of revision with excerpts from drafts of the novel. The novel itself is an account of a woman's loss and eventual recovery of a childhood vitality and sense of self. The story follows a protagonist, Anna (initially Joanna), from fearless childhood through troubled youth to adulthood. Through this narrative, I examine themes of loss, desire and identity within sexual and non-sexual relationships. After an opening passage describing an episode in childhood, the story finds Joanna at high school. Her ambivalent friendship with a classmate, Leah, and infatuation with a teenage boy, Robbie, are described. This section culminates in Robbie's drowning and Leah's disappearance. Subsequently, Joanna / Anna attends art school, where she starts an intense relationship with an older man, Alan. Her almost voyeuristic fascination with Alan is mirrored by her job photographing animals at the aquarium. Throughout, the sea and sea creatures signify those things that Anna both desires and fears. Leah returns, moves in with Anna, and eventually seduces Alan. Anna takes revenge by creating a photographic collage; through this act she symbolically "kills" her lover. In doing so, she frees herself from a damaging relationship, and is able to re- enter her life rejuvenated.